A Social entrepreneurship initiative in Batu Pahat to address economic challenges of single mothers - Adi Syahid Mohd Ali,; Zolhafizi Jaidi,; Mohd Azham Azmi,; Nur Ilyani Ramli,; Muhamad Faris Mohd Hisam,; Naqibah Azman,; Muhamad Nor Shahid Nornasir,; Muhammad Noh Haqqem Mohd Hussain,; Alif Qusyairi Abd Razak,; Ahmad Hazly Ahmad Zainuddin,; Nurul Adila Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social entrepreneurship is a critical sector for addressing social and environmental challenges. As an educational institution, Universiti Tun Hussein Onn Malaysia (UTHM) recognises its role in enabling students to become problem solvers and innovators in tackling these issues. This paper aims to describe a program established in a residential hall to solve the economic challenges of single mothers in the Batu Pahat area. To effectively achieve this goal, an emphasis was placed on organised development procedures and creative strategies. The paper extensively explains the social entrepreneurship project development process, including early planning, identification of economic concerns encountered by the single mothers in Batu Pahat, and actions taken to solve these problems effectively. Through four linked approaches, the program harnesses cooking talents, instils entrepreneurship, boosts product durability, and forges a sustainable business model. These methodologies include Potential Mapping, Innovation, Capacity Building, and Business Model Development. The project's accomplishments are detailed with relevant data and statistics to indicate the beneficial impact achieved in improving the economic position of single mothers in the region. The success of this initiative will serve as an inspiration for other social entrepreneurship projects addressing social and economic challenges in the communities. Finally, social entrepreneurship is critical in tackling social and environmental challenges. It is anticipated that the insights gathered in this paper will inspire and guide future social entrepreneurship ventures to better success in addressing pertinent social and economic challenges.